Organocatalysis: A Revolutionary Approach in Organic Synthesis - Ahmad, Kabiru Bashir; Chinedu, Emmanuel Kinsley; Pambani, Reuben; Adam, Ansar Bilyaminu; Abubakar, Musa Yahaya; Shamsuddeen, Ruslan (Darul Yasin Al Sys, 2024)
Organocatalysis has emerged as a powerful tool in organic synthesis, enabling the efficient and selective formation of complex molecules. This review highlights the recent advances in organocatalysis, including the development of new catalysts, reactions, and applications. The advantages and limitations of organocatalysis are discussed, and its potential for scalability and sustainability is evaluated. The review also explores the mechanistic insights and future directions in this field, demonstrating the versatility and impact of organocatalysis in modern organic synthesis. This paradigm shift not only addresses the pressing environmental challenges but also paves the way for more innovative and economically viable synthetic strategies. As a result, organic synthesis is poised to play a crucial role in advancing pharmaceuticals, materials science, and agrochemicals, driving forward a more sustainable and resilient chemical industry.